Strangulation of Upper Jejunum in Subsequent Pregnancy Following Gastric Bypass Surgery - Chen-Bin Wang; Ching-Chuan Hsieh; Chun-Hung Chen; Yu-Hsiang Lin; Chung-Yuan Lee; Chih-Jen Tseng (Elsevier, 2007)
Objective: Gastric bypass is a surgical procedure that is popularly used to treat morbid obesity. Herein, we report a woman who had a rare gastrointestinal complication during the subsequent antepartum period following a gastric bypass surgery. Case Report: After a Roux-en-Y gastric bypass surgery, a 32-year-old woman had unrelenting epigastria for one week at 36 weeks' gestation. An emergency cesarean delivery, followed by laparotomy, was performed. A female neonate was delivered with Apgar scores of 8 and 9 at 1 and 5 minutes, respectively. Strangulation and gangrene of the upper jejunum caused by a fibrous band at the site of the Roux anastomosis were revealed. Segmental resection of the nonviable bowel was performed. The patient experienced a smooth postoperative course. Conclusion: The awareness of internal hernias and small bowel strangulation should be addressed when unrelenting epigastric pain is present in women after Roux-en-Y gastric bypass surgery, during their first subsequent pregnancy.